StemBond hydrogels control the mechanical microenvironment for pluripotent stem cells - Labouesse, Celine; Tan, Bao Xiu; Agley, Chibeza C.; Hofer, Moritz; Winkel, Alexander K.; Stirparo, Giuliano G.; Stuart, Hannah T.; Verstreken, Christophe M.; Mulas, Carla; Mansfield, William; Bertone, Paul; Franze, Kristian; et al. (Nature Communications, 2021)
Studies of mechanical signalling are typically performed by comparing cells cultured on soft and stiff hydrogel-based substrates. However, it is challenging to independently and robustly control both substrate stiffness and extracellular matrix tethering to substrates, making matrix tethering a potentially confounding variable in mechanical signalling investigations. Moreover, unstable matrix tethering can lead to poor cell attachment and weak engagement of cell adhesions. To address this, we developed StemBond hydrogels, a hydrogel in which matrix tethering is robust and can be varied independently of stiffness. We validate StemBond hydrogels by showing that they provide an optimal system for culturing mouse and human pluripotent stem cells. We further show how soft StemBond hydrogels modulate stem cell function, partly through stiffness-sensitive ERK signalling. Our findings underline how substrate mechanics impact mechanosensitive signalling pathways regulating self-renewal and differentiation, indicating that optimising the complete mechanical microenvironment will offer greater control over stem cell fate specification.
CRIS-Team Scopus Importer:2021-11-12